From TED to Fintech: Mining Speaker Sentiments for Insights into The Future of Finance - Cahyani, Virly; Alamanda, Dini Turipanam; Kusmiati, Eti (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This research explores the diverse perspectives of TED Talks speakers on Fintech and its role in the future of finance. This study utilizes opinion mining and InfraNodus to identify trends, similarities, differences, and viewpoints that emerged in TED Talks talk's discussions about Fintech on YouTube. The methodology involves analyzing opinions expressed by TED Talks speakers on YouTube channels using opinion mining techniques and InfraNodus tools to structure and deepen understanding of the speaker’s point of view. By examining these perspectives, this study aims to enrich the understanding of how Fintech permeates culture and influences financial perspectives. The study results classified opinions into four main categories: Fintech Access, Banking Simplify, Trust Business, and AI Transaction, which helped identify critical themes in TED Talks discussions on Fintech. These findings reflect the importance of increased access to financial services, banking innovation, and positive changes in financing. The study's implications include insights for policymakers, regulators, and industry stakeholders to develop frameworks that support financial technology development while ensuring consumer protection and security.